The influence of philosophical mentality and spiritual intelligence on creativity of employees mediated by organizational commitment - Mohammad Khalilzadeh; Arman Bahari; Mojtaba Kiaee (Creativity Studies, 2023)
The root of organizational creativity depends on employee’s creativity and any factor increasing the staff ’s creativity. In recent years, specific features of the mind and the role of emotions in people are considered a competitive advantage that has been at the center of attention by organizations. Therefore, the present study focused on the relationship between spiritual intelligence and philosophical mentality on employee creativity and the mediating role of organizational commitment. To analyze the conceptual model of research, philosophical mentality the Smith’s Wellbeing Questionnaire for Workers, spiritual intelligence King’s Questionnaire, organizational commitment Allen and Meyer’s Organizational Commitment Scale, and organizational creativity Randsip’s Creativity Questionnaire were used for collecting data. Data analysis was performed using Pearson correlation coefficient and analysis of variance. The statistical sample included 278 employees of factories located in industrial towns of Isfahan, Iran. The results indicated the positive relationships between philosophical mentality and creativity, philosophical mentality and organizational commitment, spiritual intelligence and employee creativity, spiritual intelligence and organizational commitment, organizational commitment, and employee creativity. In addition, philosophical mentality and spiritual intelligence can affect the employee’s creativity through organizational commitment as a mediator variable.